Implementasi Media Blog dalam Meningkatkan Motivasi Menulis Kreatif Berbasis Apresiatif-Komunikatif - Sri Murti; Agita Misriani (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2020)
This research aims to determine the role of blog media in increasing the communicative-aprreciation based creative writing motivation student of STKIP PGRI Lubuklinggau. This research used descriptive methods. This research will be carried out at STKIP PGRI Lubuklinggau. Sampel of this research is collage student at three semester of Indonesia Language and Literatute Educaticon Study Program with amount 19 collage student. The data result, can be explain that motivation uses blog have same portion in set every answer. Proven the quetion choose answer ”very agree” with average percentage 54,71%. AND then answer ”agree” not different with percentage of 10 quetion amounting to 45,20%. Then test result, score with the most be inthe range 75-78 as many as 8 people with persentage 42,10%. Meanwhile, for the small frequency range in the same three ranges, is 83-86, 87-90 dan 95-98 as many as 2 and percentage of 10,53 %. The next, result of interview ,it was conclusion that media blog could increase cretaive writing motivation of STKIP PGRI Lubuklinggau. Conclusion, the use of media blog can increasing the motivation for creative writing of STKIP PGRI Lubuklinggau. Keyword: Learning Media, Blog, Motivation, and Creative Writing.